A review on thermal comfort assessment in Malaysian industries - Ahmad Rasdan, Ismail; Karagaratnana, Shashi Kumar S. A.; Rozli, Zulkifli; Baba, M. Deros; Mohd Nizam A., Rahman (Penerbit Universiti Teknologi Malaysia, 2012)
In this world of advanced technology, many global organizations are realizing that the importance of their worker’s comfort level towards their performance in order to be competitive. The studies in thermal comfort allow enhancing the understanding the importance of working environment among workers and occupants from various fields. This paper is focuses on reviews of the recent studies on thermal comfort assessments at the industries in Malaysia. The findings from other researchers’ thermal comfort assessments at worldwide also reviewed together. This review would help the researchers, academicians and practitioners to take a closer look on how environmental factors affect human performance in industries and help to enhance the awareness on human comfort among all Malaysians.